Fazlur Rahman and His Enduring Legacy for Indonesian Islamic Scholarship - Wekke, Ismail Suardi (International Humanity Advance, Business & Sciences, 2025)
This article examines Fazlur Rahman's intellectual legacy and its influence on the development of Islamic thought in Indonesia. Rahman, with his neo-modernist approach, offered a "double movement"-based method of Qur'anic interpretation that emphasizes the importance of historical context and its application in the present. This study uses a qualitative approach with literature analysis, highlighting how Rahman's ideas spread to Indonesia through student networks, his works, and his direct interactions with Indonesian intellectuals. This article also documents Rahman's influence on major figures such as Nurcholish Madjid, Abdurrahman Wahid, Ahmad Syafii Maarif, and Amien Rais, as well as his contribution to the reform of Islamic education in Indonesia. The findings show that Rahman's ideas on contextual interpretation, educational reform, and the development of critical thinking have played a major role in driving the intellectual dynamics of Indonesian Islam, although they have also faced criticism and challenges in their application.